2015
DOI: 10.1186/s12877-015-0107-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of playing Nintendo Wii on depression, sense of belonging and social support in Australian aged care residents: a protocol study of a mixed methods intervention trial

Abstract: BackgroundThe proportion of people aged 65 or older is the fastest growing age group worldwide. Older adults in aged care facilities have higher levels of depression, and lower levels of social support and sense of belonging compared with older adults living in the community. Research has begun to assess the effectiveness of interventions to improve the mental health of residents and has found both cognitive and physical benefits of video game playing. The benefits of playing these games in a group may also le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
6
0
1
Order By: Relevance
“…A significant fall in the scores of GDS and BDI after the intervention was found only in the VR-game group, while the control group showed an increase in depression. The result was in line with that of the preceding study [14]. It may be explained by the fact that older people participating in the VR-gamebased intervention regarded it as leisure activity rather than as a treatment so that they enjoyed it, which led to a fall in depression.…”
Section: Discussionsupporting
confidence: 89%
“…A significant fall in the scores of GDS and BDI after the intervention was found only in the VR-game group, while the control group showed an increase in depression. The result was in line with that of the preceding study [14]. It may be explained by the fact that older people participating in the VR-gamebased intervention regarded it as leisure activity rather than as a treatment so that they enjoyed it, which led to a fall in depression.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the psychological state, Chesler et al observed a clear decrease in depression levels and greater social interaction after a 6-week rehabilitation program using Wii Fit ® games in Australian institutionalized older adults [21]. In contrast, a study carried out with 58 people who lived in a nursing home found statistically significant differences in physical appearance, but not in depression levels, after an exercise program using the Nintendo Wii Fit Plus ® video console [48].…”
Section: Discussionmentioning
confidence: 97%
“…Muitas das gerontecnologias mais empregadas (videochamadas e outros meios de comunicação, redes sociais virtuais, games, dispositivos afetivos/ ortopédicos e/ou robôs companheiros) se mostraram efetivas na redução do isolamento social dos idosos (Berg et al, 2017;Piau et al, 2014;Damant et al, 2017;Sacker et al, 2017;Chi et al, 2017;Creteh-durand et al, 2017;Chen e Schulz, 2016;Zamir et al, 2018;Chesler et al, 2015;Chopik, 2016;Hicken et al, 2016;Crétel-Durand et al, 2017;Chi et al, 2017;Petersen et al, 2017;Czaja et al, 2016;Sacker et al, 2016;Koceski e Koceska, 2016;Berg et al, 2017;Arlati et al, 2019). Esses achados são de grande importância, haja vista a significativa relação direta entre isolamento social de idosos e suicídio relatada por Tsai et al (2015) e Hao et al (2017).…”
Section: Os Descritores Controlados Utilizados Na Pesquisa Foram Retirados Da Medical Subject Headings (Mesh) Da National Library Of Mediunclassified